Oxide and Hydrogel Inverse Opals and Their Applications as Physical, Chemical and Biological Sensors - Peter Hutchison; Peter Kingshott; Aimin Yu (Sensors)
Inverse opal (IO) structures based on photonic colloidal crystal (PCC) templates are types of materials that possess unique optical properties due to their ordered arrays. These materials have the ability to manipulate the propagation of light, producing unique reflection spectra and structural colours. Due to these properties, IOs have been used as optical sensors for various applications such as the detection of physical, chemical, and biological entities. This review begins with a brief introduction of PCCs, IOs and their preparation procedures. The recent advancements in the applications of IOs for sensing temperature, pH, humidity, chemical compounds (such as organic solvents and heavy metal ions), and biological entities (such as tumour cells, viruses and bacteria) are then discussed in detail. The review also explores strategies and techniques aimed at enhancing the sensitivity and lowering the limit of detection of IO-based sensors. Finally, it addresses the current challenges, existing limitations, and prospective future directions in the development and deployment of IO-based sensors.